A Marine-Buoy-Mounted System for Continuous and Real-Time Measurment of Seafloor Crustal Deformation - Tadokoro, Keiichi; Kinugasa, Natsuki; Kato, Teruyuki; Terada, Yukihiro; Matsuhiro, Kenjiro (Frontiers in Earth Science, 2020)
In this paper, we describe the development of a continuous real-time system capable of measuring seafloor crustal deformation using the GNSS/Acoustic technique and a moored buoy. A program was implemented on the buoy to automatically distinguish the onset of a direct acoustic wave even if that wave had been contaminated with reflected waves and to compress the acoustic data prior to transmission over a satellite link to the ground base station. We conducted an operations test for a total of 106 d and found that the acoustic ranging and data transmissions were frequently interrupted by an unstable power supply, resulting in only 21 % of the transmitted data being received at the ground base station. Nevertheless, the acoustic ranging measurements continued successfully as long as power was supplied.